Research of Pronoun Renjia in Semantic and Rhetorical Function - Sofi Zhang (Bina Nusantara University, 2013)
Pronoun renjia is a personal pronoun and its basic functions similar to “other people”. But, in the actual use of pronoun renjia, it can refer to the third person “he, she, they”, refers to the second “you”, and refers to the first person